« first day (505 days earlier)      last day (1078 days later) » 

04:00
in Mathematics, 8 hours ago, by MatheinBoulomenos
the version for finite Galois extension is: if $L/K$ is a finite Galois extension with Galois group $G$, then if we consider the category $L^*[G]$-Mod which consists of $L$-vector spaces together with a semilinear $G$-action, then $L^*[G]$-Mod is equivalent to k-Mod via thefunctors $V \mapsto V^G$ and $W \mapsto L\otimes_K W$
in Mathematics, 8 hours ago, by MatheinBoulomenos
that's actually an equivalence of symmetric monoidal categories if we equip $L^*[G]$-Mod with the tensor product over $L$ and $K$-Mod with the tensor product over $K$
in Mathematics, 8 hours ago, by MatheinBoulomenos
thus by abstract nonsense, you also get an equivalence of the corresponding categories of monoid objects and commutative monoid objects
in Mathematics, 8 hours ago, by MatheinBoulomenos
which are $K$-algebras and $L$-algebras with a semilinear $G$-action by ring automorphisms (respectively the commutative ones for commutative monoid objects)
in Mathematics, 8 hours ago, by MatheinBoulomenos
and then continuing by abstract nonsense, you get a category equivalence of the corresponding cogroup objects in commutative $K$-algebras which are dual to affine algebraic groups
in Mathematics, 8 hours ago, by MatheinBoulomenos
there's also some Galois descent for projective varieties, but that's harder
let $V$ be a $L^\ast[G]$-module. We need to show that there is an isomorphism $V \to L \otimes_K V^G$ of $L^\ast[G]$-modules
04:19
maybe the inverse direction is easier
$L \otimes_K V^G \to V$
does $b \otimes a \mapsto ba$ work?
Conrad claims that this works
and the proof is interesting
let $v_1, \cdots, v_n$ be $K$-linearly independent vectors in $V^G$
suppose $a_1 v_1 + \cdots a_n v_n = 0$
so for each $\sigma \in G$ we have $(a_1 - \sigma(a_1)) v_1 + \cdots + (a_n - \sigma(a_n)) v_n = 0$
WLOG $a_n = 1$, so actually we have $(a_1 - \sigma(a_1)) v_1 + \cdots + (a_{n-1} - \sigma(a_{n-1})) v_{n-1} = 0$
this is a shorter relation, so by induction we have $a_i = \sigma(a_i)$
so each $a_i \in L^G = K$ to start with
so $a_i = 0$
hey I never knew Galois descent's proof is this short
wait it isn't done, we need to show that the action is preserved
so we need to show that $\sigma(a)v = \sigma(av)$
this is clear since $v = \sigma(v)$
ok so this is short
oh there's a slick proof to show that $[L:K](\dim V^G) = \dim V$
consider the projection map $V \to V^G$ sending $v$ to $\sum_\sigma \sigma(v)$
actually it's not a projection map
ok if we're in char. coprime to $[L:K] =: n$ then we can send $v$ to $\frac1n \sum_\sigma \sigma(v)$
I'll come back to this argument later (Conrad didn't use this)
 
2 hours later…
06:15
there is something to complete in this proof, I don't have the time
Galois descent is a special case of Morita equivalence of matrix algebra!
$L^\ast[G] = \operatorname{End}_K(L)$ as rings
 
2 hours later…
08:46
in Mathematics, yesterday, by MatheinBoulomenos
@LeakyNun let $L/K$ a Galois extension with $G=\mathrm{Gal}(L/K)$ and let $f \in H^2(G,L^\times)$ a 2-cocycle, then we can construct a central simple algebra over $K$ like this. Take as a set the group algebra $L[G]$ and define the multiplication based on the relations $\lambda \cdot \sigma = \sigma \cdot \sigma(\lambda)$ and $\sigma \cdot \tau = (\sigma \circ \tau) f(\sigma,\tau)$
I still don't understand why it is $\lambda \cdot \sigma = \sigma \cdot \sigma(\lambda)$ instead of the other way round
given a $L$-vec with $G$-semilinear action we define $(b \sigma)(v) = b \sigma(v)$
then $(a\sigma)((b\tau)(v)) = (a\sigma)(b\tau(v)) = a \sigma(b) \sigma(\tau(v)) = (a\sigma(b)\cdot(\sigma\circ\tau))(v)$
so $(a \sigma) \cdot (b \tau) = a \sigma(b) \cdot \sigma \cdot \tau$
so $\sigma \cdot b = \sigma(b) \cdot \sigma$?
we want this to be an $L$-algebra
which it is
I don't see why this fails
also this is isomorphic to $\operatorname{End}_K(L)$ as rings so
09:52
@MatheinBoulomenos
10:02
@LeakyNun oh
maybe I misremembered
I just wanted the natural map to $\mathrm{End}_K(L)$ to be an isomorphism
but I think for that you need $\sigma \cdot \lambda =\sigma(\lambda) \sigma$ lol
I'm stupid
@LeakyNun I'm also not sure if we want $\sigma \cdot \tau = (\sigma \circ \tau) f(\sigma,\tau)$ or with the $f(\sigma,\tau)$ on the other side
one of those works
Let's see: we need associativity, so we want
@LeakyNun btw: this construction does not produce an $L$-algebra
the center is $K$, not $L$
okay I think what I gave just gives a construction of the opposite algebra
so I think it should be $\sigma \cdot \tau= f(\sigma,\tau) (\sigma \circ \tau)$ if you want $\sigma \cdot \lambda = \sigma(\lambda) \sigma$.
let's check that this satisfies associativity:
$(\sigma \cdot \tau) \cdot \theta = (f(\sigma,\tau) (\sigma \circ \tau)) \cdot \theta = f(\sigma,\tau) f(\sigma \circ \tau, \theta) (\sigma \circ \tau \circ \theta)$
on the other hand $\sigma \cdot (\tau \cdot \theta)=\sigma \cdot (f(\tau,\theta) \cdot (\tau \circ \theta))= \sigma(f(\tau,\theta)) \sigma \cdot (\tau \circ \theta)= \sigma(f(\tau,\theta)) f(\sigma,\tau \circ \theta) (\sigma \circ \tau \circ \theta)$
so we want $f(\sigma,\tau)f(\sigma \circ \tau,\theta)=\sigma(f(\tau,\theta))f(\sigma,\tau \circ \theta)$
$d^2(f)(\sigma,\tau,\theta)=\sigma(f(\tau,\theta)) \cdot f(\sigma \circ \tau,\theta)^{-1} \cdot f(\sigma,\tau \circ \theta) \cdot f(\sigma,\tau)^{-1}$
so it all works out
10:48
@MatheinBoulomenos oh and which book can I find this in?
some books don't give explicit formulas
and proceed via PGL
11:11
idk
just work it out yourself
I'm not sure if you can totally avoid PGL
well I want to cite it...
I think there are some explicit formulas in Jacobson - Basic Algebra 2
iirc
I've never seen the generalized form of Galois descent written down anywhere
@MatheinBoulomenos je n'ai pas le tems
do you mean "temps"?
that's how Galois wrote it
11:14
okay
I'm pretty sure it's "temps" in modern French
maybe Galois made a typo
yes, he misspelled it
guess why
because il n'avait pas le temps
parce qu'il n'avait pas le temps?
damn it
ok P.472 contains the formulas $\sigma \cdot \tau = f(\sigma, \tau) (\sigma \circ \tau)$ and $\sigma \cdot \lambda = \sigma(\lambda) \cdot \sigma$
thank you
 
8 hours later…
19:34
so we have two resolutions of $\Bbb Z$ as a $\Bbb Z[G]$-module where $G=C_n$
$\cdots \to \Bbb Z[G] \xrightarrow N \Bbb Z[G] \xrightarrow{g-1} \Bbb Z[G] \xrightarrow N \Bbb Z[G] \xrightarrow{g-1} \Bbb Z[G] \xrightarrow \varepsilon \Bbb Z \to 0$
$\cdots \to \Bbb Z[G^5] \to \Bbb Z[G^4] \to \Bbb Z[G^3] \to \Bbb Z[G^2] \to \Bbb Z[G^1] \to \Bbb Z \to 0$
if you want Tate cohomology, you can just take $\dots \to \Bbb Z[G] \xrightarrow{N} \Bbb Z[G] \xrightarrow{g-1} \Bbb Z[G] \xrightarrow{N} \Bbb Z[G] \to \dots$
19:41
I've forgotten the maps
you map $(1, g_1, g_1 g_2, \cdots)$ to $(1, g_1, g_1 g_2, \cdots)$?
that doesn't have $d^2=0$
ok the last map is still $\varepsilon$
you have some alternating sum
$(g_1, \dots, g_n) \mapsto \sum_{j=1}^n (-1)^{j+1}(g_1,g_2, \dots, \widehat{g_j}, \dots, g_n)$
oh, that one
nice
now I want maps downwards
they exist by general nonsense about projective objects
why would you want to write them down?
because I'm an explicit guy
since $\Bbb Z[G]$ is rank 1 it suffices to specify where $1$ gets sent to
there's a more useful explicit isomorphism than the one you get by a construction like that
19:54
what is it?
$d(g,1) = g-1$ btw
as a special case of Tate-Nakayama, if you fix a generator of $\alpha \in H^2(C_n,\Bbb Z)$ (which is just cyclic of order $n$ again), then for all $C_n$-modules $M$ and all $k \in \Bbb Z$, the map $\beta \mapsto \beta \cup \alpha:\widehat{H}^k(C_n,M) \to \widehat{H}^{k+2}(C_n,M)$ is an isomorphism
this is nice and useful because cup products satisfy various compatibilities with restriction/corestriction/induction/coinduction
but I want a cocycle $C_n^k \to M$
the cup product is defined on the level of cocycles
oh nice
@MatheinBoulomenos what's the formula?
CF writes: let $\varphi: A \otimes B \to C$, then $\widehat{H}^p(G,A) \otimes \widehat{H}^p(G,B) \to \widehat{H}^p(G,C)$ is given by $a \otimes b \mapsto \varphi^\ast(a.b)$
this is tautological, this isn't the formula I want
$\cup:C^n(G,A) \times C^k(G,B) \to C^{n+k}(G,A \otimes B)$
$(f \cup f')(g_1, \dots, g_n,g_{n+1}, \dots, g_{n+k})=f(g_1, \dots, g_n) \otimes g_1g_2 \dots g_n f'(g_{n+1}, \dots, g_{n+k})$

« first day (505 days earlier)      last day (1078 days later) »